An international consensus definition for contextual factors: findings from a nominal group technique - Chad E. Cook; Chad E. Cook; Chad E. Cook; Antoine Bailliard; Antoine Bailliard; Jennifer A. Bent; Joel E. Bialosky; Joel E. Bialosky; Elisa Carlino; Luana Colloca; Jorge E. Esteves; Jorge E. Esteves; et al. (Frontiers in Psychology, 2023)
ObjectiveEmerging literature suggests contextual factors are important components of therapeutic encounters and may substantially influence clinical outcomes of a treatment intervention. At present, a single consensus definition of contextual factors, which is universal across all health-related conditions is lacking. The objective of this study was to create a consensus definition of contextual factors to better refine this concept for clinicians and researchers.DesignThe study used a multi-stage virtual Nominal Group Technique (vNGT) to create and rank contextual factor definitions. Nominal group techniques are a form of consensus-based research, and are beneficial for identifying problems, exploring solutions and establishing priorities.SettingInternational.Main outcome measuresThe initial stages of the vNGT resulted in the creation of 14 independent contextual factor definitions. After a prolonged discussion period, the initial definitions were heavily modified, and 12 final definitions were rank ordered by the vNGT participants from first to last.ParticipantsThe 10 international vNGT participants had a variety of clinical backgrounds and research specializations and were all specialists in contextual factors research.ResultsA sixth round was used to identify a final consensus, which reflected the complexity of contextual factors and included three primary domains: (1) an overall definition; (2) qualifiers that serve as examples of the key areas of the definition; and (3) how contextual factors may influence clinical outcomes.ConclusionOur consensus definition of contextual factors seeks to improve the understanding and communication between clinicians and researchers. These are especially important in recognizing their potential role in moderating and/or mediating clinical outcomes.